The Golden compass - Pullman, Philip 1946- (New York Yearling, 2005)
Accompanied by her daemon, Lyra Belacqua sets out to prevent her best friend and other kidnapped children from becoming the subject of gruesome experiments in the Far North.
Prequel: Once upon a time in the North.
Keywords: Fantasy; Missing persons -- Fiction; Kidnapping -- Fiction; Arctic regions -- Fiction